الخيارات المتاحة أمام العراق لتعظيم إيراداته النفطية - محمد غالي راهي; معن عبود علي (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: یهدف البحث الى تحدید السبل التي یتم من خلالها تعظیم الای ا ردات النفطیة في الع ا رق، من خلال د ا رسة وتحلیل طبیعة هذه الای ا ردات واهمیتها والمخاطر التي تحیط بها، في ظل الامكانات النفطیة التي یمتلكها والظروف الاستثنائیة التي یعیشها، وبد ا رسة والتحلیل الاسواق التي یصدر الیها وتحدید الاهم منها. للوصول الى افضل السبل من اجل زیادة الای ا ردات النفطیة التي تعتمد علیها الدولة بشكل كامل. وقد خلص البحث الى ان صاد ا رت النفط الخام السبیل الایسر للع ا رق من اجل زیادة الای ا ردات النفطیة. وان كان هذا لا یتنافى مع الاهتمام بصناعات اخرى تستخدم النفط او منتجاته كمدخلات. وكذلك اقامة صناعة تكریریة للاستخدام المحلي. The available options for Iraq to maximize oil revenues Abctract: The aim of the research to identify ways in which to maximize oil revenues in Iraq, through the study and analysis of the nature of this income and its relevance and risks that surround it, in the oil, which is owned by special circumstances experienced by the market, and to study and analysis to determine the most important of them. To reach the best ways for increasing oil revenues, which depend on the State in full. The research concluded that the exports of crude oil the way left Iraq for increasing oil revenues.